Metal-Adapted Bacteria Isolated From Wastewaters Produce Biofilms by Expressing Proteinaceous Curli Fimbriae and Cellulose Nanofibers - Mosharaf, M. K.; Tanvir, M. Z. H.; Haque, M. M.; Haque, M. A.; Khan, M. A. A.; Molla, A. H.; Alam, Mohammad Z.; Islam, M. S.; Talukder, M. R. (Frontiers in Microbiology, 2018)
Bacterial biofilm plays a pivotal role in bioremediation of heavy metals from wastewaters. In this study, we isolated and identified different biofilm producing bacteria from wastewaters. We also characterized the biofilm matrix [i.e., extracellular polymeric substances (EPS)] produced by different bacteria. Out of 40 isolates from different wastewaters, only eleven (27.5%) isolates (static condition at 28ºC) and nine (22.5%) isolates (agitate and static conditions at 28ºC and 37ºC) produced air-liquid (AL) and solid-air-liquid (SAL) biofilms, respectively only on salt-optimized broth plus 2% glycerol (SOBG) but not in other media tested. Biomass biofilms and bacteria coupled with AL biofilms were significantly (P≤0.001) varied in these isolates. Escherichia coli (isolate ENSD101 and ENST501), Enterobacter asburiae (ENSD102), Enterobacter ludwigii (ENSH201), Pseudomonas fluorescens (ENSH202 and ENSG304), uncultured Vitreoscilla sp. (ENSG301 and ENSG305), Acinetobacter lwoffii (ENSG302), Klebsiella pneumoniae (ENSG303) and Bacillus thuringiensis (ENSW401) were identified based on 16S rRNA gene sequencing. Scanning electron microscope (SEM) images revealed that biofilm matrix produced by E. asburiae ENSD102, uncultured Vitreoscilla sp. ENSG301, A. lwoffii ENSG302 and K. pneumoniae ENSG303 are highly fibrous, compact and nicely interlinked as compared to the biofilm developed by E. ludwigii ENSH201 and B. thuringiensis ENSW401. X-ray diffraction (XRD) results indicated that biofilm matrix produced by E. asburiae ENSD102, uncultured Vitreoscilla sp. ENSG301 and A. lwoffii ENSG302 are non-crystalline amorphous nature. Fourier Transform Infrared (FTIR) spectroscopy showed that proteins and polysaccharides are the main components of the biofilms. Congo red binding results suggested that all these bacteria produced proteinaceous curli fimbriae and cellulose-rich polysaccharide. Production of cellulose was also confirmed by Calcofluor binding- and spectrophotometric assays. E. asburiae ENSD102, Vitreoscilla sp. ENSG301 and A. lwoffii ENSG302 were tested for their abilities to form the biofilms exposure to 0 to 2000 mg/L of copper sulphate (for Cu), zinc sulphate (for Zn), lead nitrate (for Pb), nickel chloride (for Ni) and potassium dichromate (for Cr), several concentrations of these metals activated the biofilm formation. The polysaccharides is known to sequester the heavy metals thus, these bacteria might be applied to remove the heavy metals from wastewater.